НЕКОИ ИМАГОЛОШКИ ПОСТАПКИ ВО МАКЕДОНСКАТА И ВО БУГАРСКАТА ЛИТЕРАТУРА НА ДИЈАСПОРА ОД ПЕРИОДОТ НА ТРАНЗИЦИЈАТА (Philological Studies, 2019)
The paper explores some theoretical aspects of diasporic literature from the period of transition. Created outside the author’s native ethnic and lingual area, this literature is based on narratives about migrations undertaken for different existential reasons. The analysis of the novels The Snow in Casablanca (2007) by Kica B. Kolbe and The Diary of a Butterfly (2008) by Krassimir Damianov is focused on the presentations of other places, away from the respective author’s homeland, and of ways of behaving which arise from an acceptance or a rejection of the cultural codes.
Keywords: литература на дијаспора, идентитети, друг/другост, имагологија, транзиција